Molecular cloning and sequence of cDNA encoding the pyrophosphate-energized vacuolar membrane proton pump of Arabidopsis thaliana. - Sarafian, V (1992)
The energy-dependent transport of solutes across the vacuolar membrane (tonoplast) of plant cells is driven by two H+ pumps: a vacuolar ("V-type") H(+)-ATPase (EC 3.6.1.3) and a H(+)-translocating (pyrophosphate-energized) inorganic pyrophosphatase (H(+)-PPase; EC 3.6.1.1). The H(+)-PPase, like the V-type H(+)-ATPase, is abundant and ubiquitous in the vacuolar membranes of plant cells, and both enzymes make a substantial contribution to the transtonoplast H(+)-electrochemical potential difference. Here, we report the cloning and sequence of cDNAs encoding the tonoplast H(+)-PPase of Arabidopsis thaliana. The protein predicted from the nucleotide sequence of the cDNAs is constituted of 770 amino acids and has a molecular weight of 80,800. It is a highly hydrophobic integral membrane protein, and the structure derived from hydrophilicity plots contains at least 13 transmembrane spans. Since the tonoplast H(+)-PPase appears to be constituted of one polypeptide species and genomic Southern analyses indicate that the gene encoding the Mr 80,800 polypeptide is present in only a single copy in the genome of Arabidopsis, it is suggested that the H(+)-PPase has been cloned in its entirety. The lack of sequence identities between the tonoplast H(+)-PPase and any other characterized H+ pump or PPi-dependent enzyme implies a different evolutionary origin for this translocase.